2016
DOI: 10.1158/1055-9965.epi-15-1326
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patient and Contextual Characteristics on Racial/Ethnic Disparity in Breast Cancer Mortality

Abstract: Background Racial/ethnic disparity in breast cancer-specific mortality in the U.S. is well documented. We examined whether accounting for racial/ethnic differences in the prevalence of clinical, patient, and lifestyle and contextual factors that are associated with breast cancer-specific mortality can explain this disparity. Methods The California Breast Cancer Survivorship Consortium combined interview data from six California-based breast cancer studies with cancer registry data to create a large racially … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Furthermore, this study was limited by the unidimensional measure of neighborhood SES that was used. Although neighborhood poverty is a valid measure of area-level SES [ 20 , 47 ], other factors that were not accounted for (such as those described above) may play an important role which was not captured here [ 48 ]. In addition, there is evidence that neighborhood characteristics as perceived by the individual living within the neighborhood may better predict some health outcomes than those captured by census-level variables alone [ 18 , 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study was limited by the unidimensional measure of neighborhood SES that was used. Although neighborhood poverty is a valid measure of area-level SES [ 20 , 47 ], other factors that were not accounted for (such as those described above) may play an important role which was not captured here [ 48 ]. In addition, there is evidence that neighborhood characteristics as perceived by the individual living within the neighborhood may better predict some health outcomes than those captured by census-level variables alone [ 18 , 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic variables were then added to the baseline model one by one to test their influence on the racial survival disparities, that is, the changes in HRs for race from the baseline model. The significance of the HR changes was evaluated with a previously developed approximate likelihood ratio–based test termed disparity χ 2 32 . The prognostic variables were ranked in order of the significance of the HR changes in all samples.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of associations between zip-code level racial and economic segregation and preterm birth and infant mortality in California showed that women and infants in less privileged zip codes were at increased odds for these adverse outcomes [47]. The contributions of such multilevel resources have also been demonstrated in other areas of health; in particular, this is an emerging area of research in cancer epidemiologic studies [48,49].…”
Section: Discussionmentioning
confidence: 99%